The Effect of Heritage, Hospitality, And E-Wom on Decisions Through Satisfaction as Intervening Variables in Chinatown Glodok, West Jakarta - Nurbaeti, Nurbaeti; Rahmanita, Myrza; Amrullah, Amrullah; Ratnaningtyas, Heny (Journal of Business on Hospitality and Tourism, 2022)
The quality of the cultural tourist attraction of Chinatown Glodok still has several problems. It is caused by several factor including heritage, hospitality, and E-WOM. This study aims to analyses the effect of heritage, hospitality, and E-WOM on visiting decisions through visitor satisfaction as an intervention in Chinatown Glodok, West Jakarta. This type of research uses descriptive quantitative. The sample amounted to 200 people. The sampling technique used was accidental sampling. The research method uses path analysis with the help of the Smart PLS program with measurement model analysis (outer model) and structural model analysis (inner model). The results showed that: (1) Heritage and hospitality had a significant effect on visitor satisfaction; (2) E-WOM has no significant effect on visitor satisfaction; (3) Heritage, hospitality, and visitor satisfaction have a significant effect on visiting decisions; (4) E-WOM has no significant effect on visiting decisions; (5) Heritage and hospitality have a significant effect on visiting decisions through visitor satisfaction; (6) E-WOM has no significant effect on visiting decisions through visitor satisfaction.